The Role of Village Surveillance Officer to Prevent Dengue Hemorrhagic Fever - Sunarsih Sunarsih; Kuntoro Kuntoro; Chatrin U.W; Nugroho Susanto (International Journal of Public Health Science (IJPHS), 2016)
Dengue is a major public health problem in Indonesia. The program of elimination of mosquito breeding places is still low. This study was aimed to analyze the effectiveness of village surveillance officer for decrease container index. Study design was quasy experiment. The intervention included: community workshops; community involvement in clean-up campaigns; and distribution of information, education and communication materials in the village surveillans officer. Data were analyzed with t test, and path way analyzed. There is significantly differences knowdlege, attitude, behaviour, sanitation, and container index p<0.05. Based on the path analysis was concluded that village surveillance officer increased knowledge, attitude, behavior, sanitation and container index.Surveillance village officer is concluded to be more effectively decreased of larva index through comunity behavior. Surveillance village officer is important because it effectively the coverage of larva index through community behaviour participation.